Cauda Equina Syndrome due to Multiple Myeloma: A Case Report (Bangladesh Journal of Neuroscience, 2014)
Cauda equina compression following vertebral compression fractures or vertebral plasmacytomas is relatively uncommon presentation of multiple myeloma. Here we describe a case of cauda equina syndrome due to multiple myeloma in an elderly Bangladeshi male who presented with difficulty in walking, urinary complaints & unexplained weight loss. CT guided FNAC from lesion of spine, bone marrow study, skeletal survey, MRI of spine & immune electrophoresis confirmed the diagnosis of multiple myeloma. We treated the patient with radiotherapy, dexamethasone, antimyeloma therapy, physiotherapy & bisphosphonates in collaboration with hematologists & neurosurgeons. He showed significant improvement both clinically & biochemically in the follow up.Bangladesh Journal of Neuroscience 2014; Vol. 30 (1): 57-61